2020
DOI: 10.3390/cancers12010177
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mTOR and PTEN to Radioresistance in Sporadic and NF2-Associated Vestibular Schwannomas: A Microarray and Pathway Analysis

Abstract: The use of radiation treatment has increased for both sporadic and neurofibromatosis type 2 (NF2)-associated vestibular schwannoma (VS). However, there are a subset of radioresistant tumors and systemic treatments that are seldom used in these patients. We investigated molecular alterations after radiation in three NF2-associated and five sporadically operated recurrent VS after primary irradiation. We compared these findings with 49 non-irradiated (36 sporadic and 13 NF2-associated) VS through gene-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…Furthermore, the same tumors demonstrated downregulation of phosphate and tensin homolog (PTEN) signaling; PTEN downregulation leads to increased mTORC1 signaling via overactivation of the AKT/PKB pathway. Together, these findings suggest that increased mTORC1 activity plays a key role in VS radioresistance 95 . Mutations affecting the mTOR and PTEN pathway may therefore play a role in tumor transformation leading to recurrence or treatment escape following radiation therapy.…”
Section: Vestibular Schwannoma Radiobiologymentioning
confidence: 86%
“…Furthermore, the same tumors demonstrated downregulation of phosphate and tensin homolog (PTEN) signaling; PTEN downregulation leads to increased mTORC1 signaling via overactivation of the AKT/PKB pathway. Together, these findings suggest that increased mTORC1 activity plays a key role in VS radioresistance 95 . Mutations affecting the mTOR and PTEN pathway may therefore play a role in tumor transformation leading to recurrence or treatment escape following radiation therapy.…”
Section: Vestibular Schwannoma Radiobiologymentioning
confidence: 86%
“…[ 26 ] The expression of three collagen family genes (COL5A1, COL3A1, and COL4A1) was negatively correlated with the expression of NPY, which was found to promote the migration of macrophages in collagen in vitro [ 27 ]. The crosstalk between collagen production and radiotherapy has been studied extensively [ 16 , 17 ]. We have revealed an important function of these four collagen family genes ( COL5A1 , COL3A1 , COL4A1 , and COL15A1 ) in VS, and their high expression may be associated with VS radiotherapy recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if the molecular biological features associated with VS recurrence can be identified, more precise VS treatments can be achieved. The GSE141801 dataset from the Gene Expression Omnibus (GEO) database analyzes the transcriptomic profile of tumors between patients with VS who relapsed after radiation therapy alone and another group of patients who underwent direct surgery without radiation therapy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective investigation comparing 8 irradiated and 49 nonirradiated VS, Gugel et al found that progressive NF2-associated VS after irradiation demonstrated downregulation of phosphatase and tensin homolog (PTEN) and upregulation of mTOR signaling. These findings suggest that NF2-associated VS may resist radiation by downregulating the tumor suppressor PTEN while promoting PI3K/Akt signaling and overexpression of mTOR [ 215 , 216 ]. Because PTEN can initiate cell cycle arrest by inhibition of cyclin D [ 217 ], downregulation of PTEN may lead to radiation resistance in VS by promoting cell cycle progression and cell proliferation.…”
Section: Radiobiology and Radiation Resistance In Vestibular Schwannomamentioning
confidence: 99%